A Little Book about BIG Chemistry : The Story of Man-Made Polymers - Massy, Jim (SpringerBriefs in Materials,, 2017)
The brief explains in simple terms the essentials of polymer chemistry and how polymers came to be discovered by pioneers in this field. It relates the many uses of polymers, including those not widely recognised by the lay person. The chemistry of polymerisation and the influence of chemical structure and additives on properties are described. Ethical issues are considered, especially in the context of huge tonnages of plastics. Finally short paragraphs on more than 30 common polymers are listed chronologically with chemical structures, properties and applications. It will appeal to those with connections to or within the plastics, rubber and textile industries, science students, members of other science disciplines using polymers, as well as people just curious to know about everyday plastics.